2021
DOI: 10.1111/iwj.13552
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of perforator flaps in plantar defects: Risk analysis of complications

Abstract: The purpose of this study was to identify the risk factors for complications of perforator flaps in plantar reconstruction. A systematic review was performed by searching the PubMed, Cochrane Library, MEDLINE, and EMBASE databases from their inception date up to October 2020. Only studies on reconstructing plantar defects with perforator flaps were included, and specific data were required for each patient in the included studies. A total of 14 studies involving 111 flaps were identified and included in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…limited tissue perfusion may be a result of damage in the macrocirculation or microcirculation. Diabetic patients are more prone to dangerous infections, rendering the healing of wounds more problematic and this also was reported by Zhang et al, in his study on perforator flaps [9].…”
Section: Discussionsupporting
confidence: 61%
“…limited tissue perfusion may be a result of damage in the macrocirculation or microcirculation. Diabetic patients are more prone to dangerous infections, rendering the healing of wounds more problematic and this also was reported by Zhang et al, in his study on perforator flaps [9].…”
Section: Discussionsupporting
confidence: 61%
“…On the contrary, Zhang et al . reported that a flap size greater than 50 cm 2 was associated with a higher postoperative complication rate [ 25 ]. Considerable perforator flap complications may be related to inadequate vascular supply; such an issue is problematic to many surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the donor site's aesthetic and normal function is also a struggle when a vast perforator flap is required. A large pedicled perforator flap donor site may be aesthetically acceptable in older patients with sagging skin; however, it may be unsightly in younger patients [ 12 , 25 ]. When the flap size is greater than 50 cm 2 , it is recommended that surgeons consider different treatment modalities, their experience, and the holistic assessment of the patient's condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complications of nasolabial perforator flaps include postoperative congestion or ischemia, and some flaps require secondary debulking or pedicle division surgery. Previous studies have shown that Type 2 diabetes mellitus, elderly age, large flap size, and other factors can affect the blood supply of the flap in plantar reconstruction 1,2 . Currently, no studies have focused on identifying the risk factors of complications and secondary surgery with nasolabial perforator flaps in nasal reconstruction.…”
Section: Introductionmentioning
confidence: 99%